2006
DOI: 10.1007/s00256-006-0169-2
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal osteoblastoma: report of a case with a rare histopathologic presentation and review of the literature

Abstract: Osteoblastoma is an uncommon benign bone tumor most commonly located in the vertebral column or metaphysis of a long bone. Periosteal location is rare. We report a periosteal-based osteoblastoma, arising from the proximal tibia, in a 20-year-old woman who presented with knee swelling and pain of 2-year duration. Imaging studies showed a metaphyseal surface-based lesion with patchy radiodensities. The cortico-medullary junction was intact. The lesion was totally excised. Histopathologic evaluation disclosed imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…[6] Sometimes cartilage is seen. [7] In the present case secondary ABC like areas and cartilage was seen which is uncommon. The tumor does not permeate into the adjacent bony trabaculae and the mitotic activity is low.…”
Section: Case Reportsupporting
confidence: 43%
“…[6] Sometimes cartilage is seen. [7] In the present case secondary ABC like areas and cartilage was seen which is uncommon. The tumor does not permeate into the adjacent bony trabaculae and the mitotic activity is low.…”
Section: Case Reportsupporting
confidence: 43%
“…Osteoblastoma is a rare osteoblastic benign bone tumor that most frequently affects the vertebral column and sacrum, but it may virtually affect any bone in the body (1, 2). Several studies demonstrate 34% long tubular bone involvement and 30% vertebral bone involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Its peak incidence is in the second decade, and it is rare before 10 years and after 30 years of age (1). For many years osteoblastoma was named as giant osteoid osteoma denoting its histopathological similarity with osteoid osteoma but it reveals a larger nidus (2, 3). Lesions with a nidus size more than 2 cm are considered as osteoblastoma (1-4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study of osteosarcoma of the mandible indicated that the use of chemotherapy was not a predictor for overall survival in a multivariate analysis [13]. More importantly, parosteal or periosteal osteogenic sarcomas, typically arising from the surface of bones, often times is a low-grade lesion, and the one situation in which chemotherapy is not routinely offered [2,14].…”
Section: Prognostic Factorsmentioning
confidence: 99%